A bHLH transcription factor, SlbHLH96, promotes drought tolerance in tomato. Issue 1 (6th September 2022) - Liang, Yunfei; Ma, Fang; Li, Boyu; Guo, Cong; Hu, Tixu; Zhang, Mingke; Liang, Yan; Zhu, Jianhua; Zhan, Xiangqiang
Abstract: Drought stress caused by water deficit reduces plant productivity in many regions of the world. In plants, basic helix–loop–helix (bHLH) transcription factors regulate a wide range of cellular activities related to growth, development and stress response; however, the role of tomato SlbHLHs in drought stress responses remains elusive. Here, we used reverse genetics approaches to reveal the function of SlbHLH96, which is induced by drought and abscisic acid (ABA) treatment. We found that SlbHLH96 functions as a positive regulator of drought tolerance in tomato. Overexpression of SlbHLH96 in tomato improves drought tolerance by stimulating the expression of genes encoding antioxidants, ABA signaling molecules and stress-related proteins. In contrast, silencing of SlbHLH96 in tomato reduces drought tolerance. SlbHLH96 physically interacts with an ethylene-responsive factor, SlERF4, and silencing of SlERF4 in tomato also decreases drought tolerance. Furthermore, SlbHLH96 can repress the expression of the ABA catabolic gene, SlCYP707A2, through direct binding to its promoter. Our results uncover a novel mechanism of SlbHLH96- mediated drought tolerance in tomato plants, which can be exploited for breeding drought-resilient crops.